A career in hospitality: enjoying its benefits and living with the drawbacks - Steinbock, Erich (Henry Stewart Talks, 2023)
Followership, Leadership, Role Models, Five attributes of business, Integration strategies, Marriott International, Ritz-Carlton Hotel Company